Penggunaan Rakit Terbang Berbasis STEM untuk Mengembangkan Kemampuan Literasi Matematika Sekolah Dasar - Kristika Sari (Jurnal Didaktika Pendidikan Dasar, 2022)
Based on the PISA report that the student competencies in literacy and numeracy low, the government has begun to intensify the improvement of students' abilities in these two aspects. The purpose of this study was to develop mathematical literacy through the use of STEM-based flying rafts, to find out the practical application of using flying rafts in learning. This study uses the R&D method. Learning begins with real problems that exist in the community and explores students' ideas to solve these problems in mathematics. The results of using STEM-based flying rafts are able to develop students' mathematical literacy. This is indicated by the average value of students. The average student learning outcomes in the aspect of formulating are 93.33; in the aspect of using the average value of 91.67; and in the aspect of interpretation the average value is 88.75. Students are also happy and enthusiastic in learning to use STEM-based flying rafts.